Chlorogenic and Caftaric Acids in Liver Toxicity and Oxidative Stress Induced by Methamphetamine - Khaled M. M. Koriem; Rowan E. Soliman (Journal of Toxicology)
Methamphetamine intoxication can cause acute hepatic failure. Chlorogenic and caftaric acids are the major dietary polyphenols present in various foods. The aim of this study was to evaluate the protective role of chlorogenic and caftaric acids in liver toxicity and oxidative stress induced by methamphetamine in rats. Thirty-two male albino rats were divided into 4 equal groups. Group 1, which was control group, was injected (i.p) with saline (1 mL/kg) twice a day over seven-day period. Groups 2, 3, and 4 were injected (i.p) with methamphetamine (10 mg/kg) twice a day over seven-day period, where groups 3 and 4 were injected (i.p) with 60 mg/kg chlorogenic acid and 40 mg/kg caftaric acid, respectively, one day before methamphetamine injections. Methamphetamine increased serum aspartate aminotransferase, alanine aminotransferase, alkaline phosphatase, bilirubin, cholesterol, low-density lipoprotein, and triglycerides. Also, malondialdehyde in serum, liver, and brain and plasma and liver nitric oxide levels were increased while methamphetamine induced a significant decrease in serum total protein, albumin, globulin, albumin/globulin ratio, brain serotonin, norepinephrine and dopamine, blood and liver superoxide dismutase, and glutathione peroxidase levels. Chlorogenic and caftaric acids prior to methamphetamine injections restored all the above parameters to normal values. In conclusion, chlorogenic and caftaric acids before methamphetamine injections prevented liver toxicity and oxidative stress where chlorogenic acid was more effective.